Cumulative effects of common genetic variants on risk of sudden cardiac death. (1st June 2015) - Huertas-Vazquez, Adriana; Nelson, Christopher P.; Sinsheimer, Janet S.; Reinier, Kyndaron; Uy-Evanado, Audrey; Teodorescu, Carmen; Ayala, Jo; Hall, Alistair S.; Gunson, Karen; Jui, Jonathan; Samani, Nilesh J.; Chugh, Sumeet S.
Abstract: Background: Genome-wide association studies and candidate-gene based approaches have identified multiple common variants associated with increased risk of sudden cardiac death (SCD). However, the independent contribution of these individual loci to disease risk is modest. Objective: To investigate the cumulative effects of genetic variants previously associated with SCD risk. Methods: A total of 966 SCD cases from the Oregon-Sudden Unexpected Death Study and 1926 coronary artery disease controls from the Wellcome Trust Case–Control Consortium were investigated. We generated genetic risk scores (GRSs) for each trait composed of variants previously associated with SCD or with abnormalities in specific electrocardiographic traits such as QRS duration, QTc interval and heart rate. GRSs were calculated using a weighted approach based on the number of risk alleles weighted by the beta coefficients derived from the original studies. We also compared the highest and lowest quintiles for the GRS composed of SCD SNPs. Results: Increased cumulative risk was observed for a GRS composed of 14 SCD-SNPs (OR = 1.17 [1.05–1.29], P = 0.002). The risk for SCD was 1.5 fold greater in the highest risk quintile when compared to the lowest risk quintile (OR = 1.46 [1.11–1.92]). We did not observe significant associations with SCD for SNPs that determine electrocardiographic traits. Conclusions: A modest but significant effect on SCD risk was identified for a GRS composed of 14 previously associated SCD SNPs. While next generation sequencing methodology will continue to identify additional novel variants, these findings represent proof of concept for the additive effects of gene variants on SCD risk.